AI in Competitive Intelligence, Traditional and New Techniques for Gathering and Analysing Data - TARANU, Silvia Denisa; CIORANU, Adrian Gabriel (Journal of Environmental Management and Tourism, 2024)
In this paper we explored the relationship between Artificial Intelligence (AI) and Competitive Intelligence (CI), attempting a definition of CI that considers the various dimensions it is defined by. Thus, we delved into data collection, analysis, and how intelligence is generated. We further analysed how advanced tools and technologies such as machine learning algorithms are used to enable real-time monitoring of competitors to derive CI. Applications of AI/CI to tourism are being discussed in the context of the analysis, bringing a practical approach and insights. We completed our analysis with ethical considerations that have an impact on both the quality of the intelligence and the deeper, social implications. We concluded by proposing a practical definition of CI that incorporates the latest technological advancements, including those brought by AI, with the ultimate goal to provide a reference that ensures companies can draw the best and most reliable results from CI.